Implementassi Teknik Structural Equation Modeling untuk Meningdentifikasi User Requirements dalam Pengembangan Perangkat Lunak Knowledge Sharing System - Muhammad Ihsan Jambak (Annual Research Seminar (ARS), 2015)
User requirements identification process as one of the essential phase in software development processes, commonly using qualitative methods. It is realized, that in the qualitative methods there are several issues that could affect the final results of the user requirements data collection. Specifically on the Social Application of Information Technology where not only elements of functionality are important, the accuracy and representativeness of the users’ needs data also very are important factors. This study apply a quantitative method with Structural Equation Modeling technique in identifying the users requirements in the software development of Knowledge Sharing System. Results of this study concluded that the quantitative method with Structural Equation Modeling technique can be used to identify user needs in an effective, accurate, and precise.